Mining of Antibacterial Related BGC and Analysis of Antibacterial Mechanism At Protein Level - Tu, Haohong (International Journal of Public Health and Medical Research, 2026)
Antibacterial biosynthetic gene clusters (BGCs) are rich in new natural products, and therefore, genome mining has been used to discover them in bacteria and fungi. This paper investigates the following two problems: how to extract antibacterial BGCs efficiently, and how to understand the antibacterial mechanisms of these genes at the protein level. Based on the above analysis, a single set of discovery methods is not suitable for identifying important genes and proteins. Antibacterial activity at the protein level is generally mediated by enzymes, precursor peptides, transporters, tailoring proteins, immunity proteins and regulatory factors that regulate biosynthesis and modes of action. Based on recent studies of antiSMASH-based mining, BGC classification, proteomining and fungal and bacterial cluster characterization, a practical workflow for discovery and mechanistic interpretation has been established in this paper. Therefore, BGC mining should also investigate the origin of antibacterial functions at the protein level via biosynthetic systems, not only cluster prediction.